Learning of Spoken Language for Deaf Children with Reflective Maternal Method - Anim Purwanto; Endry Boeriswati; Fathiaty Murtadho (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Children with hearing loss experience difficulty in pronouncing vowels and words due to lack of speaking habits, especially in the family environment. This study aims to analyze the use of reflective maternal methods in improving the spoken language of deaf children at the State Special School 7 Jakarta. Qualitative descriptive research methods were used to understand this phenomenon. The data source involves one class teacher and three students with hearing impairment, with interviews, observation and documentation as methods of collecting information. The results show variations in oral language abilities through the reflective maternal method. YAS subjects have less clear articulation but use gestures to complete their communication. MSY is able to produce words and sentences but has difficulty in constructing sentences. AHS, the third subject, also has less clear articulation and uses sign language to support understanding of his interlocutor. This research makes a significant contribution to the understanding of spoken language learning of deaf children so that appropriate strategies are needed to support effective communication for each individual.